Functional Tricuspid Regurgitation in the Transcatheter Aortic Valve Replacement Population and Emerging Transcatheter Tricuspid Valve Interventions - Molly Silkowski; Payton Kendsersky; Nicholas Amoroso (US Cardiology Review)
Transcatheter aortic valve replacement (TAVR) has revolutionized the management of aortic valve disease. However, its success has brought attention to concurrent tricuspid valve disease and the inadequacy of treatments. This review explores the emerging field of transcatheter tricuspid valve interventions (TTVI) after TAVR. We address the pathophysiology and prevalence of post-TAVR tricuspid valve disease and TTVI strategies, including repair, replacement, annuloplasty, and edge-to-edge repair. We also discuss clinical studies assessing TTVI safety and efficacy, including for patients with previous TAVR. Collaboration among clinical disciplines remains crucial for advancing this emerging field to establish best practices regarding patient selection and procedural complexities.